Inhibition of angiogenesis and metastasis in colorectal cancer cell lines through KRAS-associated signaling pathways by 2-methoxy-6-undecyl-1,4-benzoquinone - Abd Rahman, Noor Izzah; Tham, Chau Ling; Abd Hamid, Roslida (Elsevier Ireland Ltd, 2024)
Colorectal cancer (CRC), the third most prevalent cancer globally, presents formidable hurdles in treatment owing to factors such as therapeutic resistance and genetic mutations affecting primary drug targets. 2-methoxy-6-undecyl-1,4-benzoquinone (BQ), derived from Ardisia crispa roots, has emerged as a potent anti-inflammatory and anti-angiogenic compound with substantial potential, as evidenced by previous studies. This study aimed to explore the potential of BQ in suppressing angiogenesis and metastasis in the human CRC cell lines LoVo and HCT116. Various in vitro and in silico studies have been conducted to elucidate the potential pathway(s) of BQ. BQ was highly cytotoxic, with an IC50 of 7.01 ± 0.6 μM in HCT116 and 9.58 ± 0.8 μM in LoVo cells. Moreover, BQ induced notable apoptotic activity and suppressed migration, invasion, and adhesion in both cell lines. The inhibition of MMP-2 suggests the potential of BQ to impede extracellular matrix degradation and CRC cell metastasis. BQ inhibits the expression of key proteins involved in angiogenesis and metastasis, including VEGF-A, VEGF-C, BRAF, ERK, KRAS, PI3K, and AKT. Molecular docking simulations illustrated the robust binding of BQ to CRC protein receptors. BQ holds promise in impeding CRC progression by targeting angiogenesis and metastasis, particularly through inhibition of the KRAS/BRAF/ERK and KRAS/PI3K/AKT signaling pathways.